Pathogen profile of co-infections and mortality determinants among patients with severe fever with thrombocytopenia syndrome - Hu, Yuan-Yuan; Xia, Guo-Mei; Zhang, Han; Zhang, Zhen-Hua (Frontiers in Cellular and Infection Microbiology, 2025)
ObjectivesSevere fever with thrombocytopenia syndrome (SFTS) poses an increasing threat to global public health. This study aimed to investigate pathogen characteristics of bacterial/fungal co-infections and determine prognostic factors for mortality in co-infected SFTS patients.MethodsDemographic and clinical data were collected for eligible SFTS patients admitted to a sentinel hospital. LASSO and multivariable logistic regression were used to identify independent predictors.ResultsA total of 629 SFTS patients were included, of whom 283 (45.0%) presented with co-infections. Most isolates (75.9%) obtained from respiratory specimens. Among 127 isolated fungi, Aspergillus fumigatus (29.9%) was predominant, followed by Candida albicans (28.3%). Of 159 bacteria, Klebsiella pneumoniae (13.8%) and Acinetobacter baumannii (13.8%) were the most common. Co-infected patients had significantly longer hospital stays, higher costs, and increased mortality. Multivariable logistic regression analysis revealed that antifungal use, transfer to the ICU, receiving CRRT, presence of central nervous system symptoms, mechanical ventilation, older age, and elevated levels of LDH were independent predictive factors of mortality risk among co-infected SFTS patients, and a nomogram was constructed. The ROC curve showed that the nomogram achieved an AUC of 0.949, and DCA confirmed the clinical utility.ConclusionThis study highlights that bacterial/fungal co-infections are highly prevalent and clinically impactful in SFTS patients, warranting enhanced microbial surveillance and targeted intervention.